IL-15-secreting γδT cells induce memory T cells in experimental allergic encephalomyelitis (EAE) mice. Issue 2 (August 2015) - Wang, Xiaoqian; Wei, Yinxiang; Liu, Xiaoling; Xing, Chen; Han, Gencheng; Chen, Guojiang; Hou, Chunmei; Dambuza, Ivy M.; Shen, Beifen; Li, Yan; Xiao, He; Wang, Renxi
Highlights: We identified a new subset of IL-15-secreting γδT (γδT15) cells. γδT15 cells were increased in EAE mice. γδT15 induced CD44 hi memory T cells by secreting IL-15. γδT15-induced memory T cells became into Th17 cells to induce EAE. Abstract: With the most recent data suggesting γδT cells as primary producers of the pro-inflammatory autoimmune-associated cytokine, the relationship between γδT cells and Th17 in experimental allergic encephalitis (EAE) mice requires more extensive investigation. By flow cytometry and qPCR, we identified a new subset of IL-15-secreting γδT (γδT15) cells that increased in EAE mice. The capacity of IL-15-secreting γδT cells inducing memory T cells and memory T cells inducing IL-17 + Th17 was examined by transferring into EAE mice and 7-week-old female nude mice, respectively. We found that γδT15 induced CD44 hi memory T cells by secreting IL-15. γδT15-induced memory T cells induced EAE by transforming into pathogenic Th17 cells. The data suggest that a new subset of IL-15-secreting γδT cells mediated the production of memory T cells which transformed into pathogenic Th17 cells in EAE mice.